Enhancement of strength and durability of fly ash concrete in seawater environments: Synergistic effect of nanoparticles. (30th October 2018) - Uthaman, Sudha; Vishwakarma, Vinita; George, R.P.; Ramachandran, D.; Kumari, Kalpana; Preetha, R.; Premila, M.; Rajaraman, R.; Mudali, U. Kamachi; Amarendra, G.
Highlights: Fly ash concrete specimens were fabricated using TiO2 and CaCO3 nanoparticles. Year-long studies in seawater showed synergistic effect nanoparticles. Nano-TiO2 showed faster hydration with more filler effects and antibacterial. Nano-CaCO3 contributed to high pH and compressive strength. 1:1 ratio of nano TiO2 and CaCO3 emerged with superior concrete properties. Abstract: Fly ash is used in concrete industry to reduce the amount of cement and to enhance the durability of concrete. Nuclear industry recently adopted fly ash concrete as a government initiative to reduce carbon footprint and also to provide an impermeable skin for the several structures in the cooling water system exposed to marine environment for enhanced durability. Earlier detailed studies on fly ash concrete has shown that despite its superiority over conventional concrete with respect to strength and durability, some concerns such as delayed setting and hydration, low early-age strength, and higher carbonation may pose a problem for its wider application. The present work is an attempt to overcome these deficiencies by nanophase modification of concrete with the incorporation of nano-titania and nano-calcium carbonate at 2% by weight of cement. Four different types of concrete mix were arrived and specimens of different sizes were cast in order to explore the various properties of concrete. After 28 days of curing in potable water, the samples were exposed to seawater at Nuclear Desalination Demonstration Plant (NDDP) sump at Kalpakkam and were withdrawn for testing at different ages like 56, 90, 180 and 365 days. Nanophase modification increased the pozzolanic activity resulting in faster hydration, early-age strength and long-term compressive and split tensile strength, permissible electrical resistivity for corrosion, lower chloride ion penetration, carbonation depth biofilm formation and higher internal pH. Among the different mixes, the synergy of 1% NC and 1% NT emerged superior with excellent concrete properties related to mechanical properties, pore structure, durability and optimum antibacterial activity.